Development of approaches to enzyme-free isolation of pancreatic islets - G. N. Skaletskaya; N. N. Skaletskiy; G. N. Bubentsova; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
The success of pancreatic islet allotransplantation in the treatment of patients with a difficult-to-manage type 1 diabetes depends mainly on the quantity and quality of islets isolated from the pancreas of deceased donors using enzyme preparations, primarily collagenase. Numerous studies on improvement and standardization of islet isolation techniques have reached their limits in the last decade. This has made it impossible to further boost the number and quality of clinical transplants. Taking into account the negative impact of collagenase technique on the morphofunctional properties of isolated islets, this work has studied the possibility of enzyme-free isolation of islet tissue purified of exocrine ballast. Experiments using the pancreas of newborn and young rabbits showed that developing methodological approaches to obtaining islet-like cultures without the use of exogenous enzymes is feasible.